Creating an Inheritor: Uniting al-Muhājir’s Migration Story Within the Spiritual Narrative Lineage of the Prophet & Ḥusayn’s Migration Stories - Madihid, Sharifah Huseinah (Universitas Islam Internasional Indonesia, 2024)
Studies on hagiographies of the migrant founder of the Bāʿalawī Hadrami and its diaspora, Aḥmad b. ʿĪsā al-Muhājir tend to be critical of them as being too descriptive or fantastical and fabricated in nature thereby rendering them otiose as subjects of study in scholarly research. Through juxtaposing these hagiographies with that of two of the most important ancestors of al-Muhājir, the Prophet Muḥammad and Ḥusayn, this article argues that the hagiographies of al-Muhājir’s migration are purposefully aligned with the migration narratives of Muḥammad and Ḥusayn in order to cement him and his descendants, the Bāʿalawīs, as the legitimate inheritors of the Prophet and his grandson in a spiritual and genealogical chain. By carefully dismantling the elements present in these three narratives, this article stresses the need to look at history beyond its factual and descriptive utility but as a tool used to create and legitimize an ideological agenda.